MOTIVASI INDONESIA MENGHENTIKAN EKSPOR MINERAL MENTAH JENIS BAUKSIT KE TIONGKOK PASCA PEMBERLAKUAN UNDANG-UNDANG MINERBA NO.4 TAHUN 2009 - Achmad Fauzi; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research would explain about Indonesia‟s government policy to stop and banned the export of raw material bauxite to Tiongkok after the enactment of the mineral and Coal Regulations Number 4/2009. This policy created a dynamic for trade relations between Indonesia and Tiongkok. Dynamics that change the orientation of bilateral relations of Indonesia-Tiongkok.To see the problem of raw material bauxite policy by Indonesia‟s government, the author uses an explanotary qualitative research methodology, the data collection techniques by library reseach are derived from sources of literature books, published magazine, journals, and scientific articles. The persepective used is Merchantilism that see the state‟s role in regulating its economy. The theory used is Foreign Policy, Prebisch-Singer theory through a strategy of less developed countries in the world look at trade patterns and use the concept of national interest.Indonesia‟s policy became implications for improved utilization and governance in natural resources of bauxite in order to achieve industrialization products (raw material bauxite) after enactment bauxite mining regulation Number 4/2009, while the implications of this policy for Tiongkok is reduced supply of bauxite from Indonesia, on the other side it is encouraging Tiongkok to Invest in the construction of smelter in Indonesia that prospects for the economy of both countries in the field of mineral and coal mines.Key words: Mining and Coal Regulations 4/2009, raw material export regulations, industrialization of bauxite.